Dayah Darussalam Network and Dayah Awakening in Aceh - Mizaj Mizaj (Budapest International Research and Critics University, 2018)
As the oldest educational institution in Southeast Asia, dayah has not received wide attention from researchers at international, national and even local levels. This paper was carried out to see the revival of Dayah in Aceh through the spread of the Dayah Darussalam network. Previously the dayah had passed the phase. First, the initial phase. This phase is marked by the establishment of Dayah Zawiyah Cot Kala in the 10th century AD. Second, the golden phase. This phase occurs around the 16-18th century. This golden phase was marked by the establishment of Dayah Manyang Baiturrahman . Third, the phase of decline. This phase began since the Dutch launched their aggression in Aceh in 1873. The phase of the decline of the dayah is marked by two things: (1) the dayah scholars split their focus between conducting educational activities and physical resistance to expel the Dutch colonizers; (2) the dayah curriculum at that time began to be limited only to religious studies. And finally the phase of the Dayah awakening marked by the spread of the Dayah Darussalam network. This can be seen from the four generations who have studied in the Dayah Darussalam. The four generations formed the Dayah Darussalam network by establishing a dayah after they finished learning in the Dayah Darussalam.